Plan de intervención para modificar esquemas desadaptativos y regulación emocional en una muestra de estudiantes universitarios. - Acosta Lalaleo, Karen Leonela (2024)
The present research had the objective of analyzing maladaptive schemas and emotional regulation in university students. The methodology presented a quantitative, non-experimental approach with a cross-sectional design and a descriptive and correlational level. The study sample was made up of 307 students from the Initial Education program at the National University of Chimborazo; 98.7% of the sample are women. Psychometric techniques were used, and the following instruments were applied. Young´s Schemas Questionnaire-Second Edition (YSQ-L2) and Emotional Relation Questionnaire (ERQ). The most relevant results indicate a significant presence of the following schemes: Emotional Inhibition 35.8%, Entitlement/Grandiosity 31.9%, Insufficient Self-control/Self-discipline 31.6% and Emotional Deprivation 30.9%. Concerning the components in 65.8%. A regulation, emotional reappraisal occurs in 72% and emotional suppression in 65.8%. A significant and direct evaluation in shown among the variables. Finally, an intervention plan was developed based on cognitive-behavioral techniques.